2013
DOI: 10.1111/eve.12019
|View full text |Cite
|
Sign up to set email alerts
|

Standing low‐field magnetic resonance imaging of a comminuted central tarsal bone fracture in a horse

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/eve.12108/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Now, with regard to the MRI, it was obtained via a low-field MRI magnet which provided us with an appropriate visualization of the normal structures of the tarsal joint. In the case of horses and dogs [4, 1315], low-field intensity protocols for the study of the tarsal joint have been reported, as well as high-field magnet studies [2, 9]. Both have provided good resolution images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, with regard to the MRI, it was obtained via a low-field MRI magnet which provided us with an appropriate visualization of the normal structures of the tarsal joint. In the case of horses and dogs [4, 1315], low-field intensity protocols for the study of the tarsal joint have been reported, as well as high-field magnet studies [2, 9]. Both have provided good resolution images.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we used pulse sequences (SE T1-weighted and GE STIR T2-weighted) that made possible for us to adequately observe the main anatomical structures of several joints (tarsocrural, intertarsal and tarsometatarsal), most noticeably in the case of the SE T1-weighted images related to the GE STIR T2-weighted images. The tarsus joints of dogs [9] and horses [4, 5, 14] have been studied by using a similar MRI sequences, although Bolt et al [15] only applied SE T1-weighted images to diagnose a central tarsal bone fracture in a horse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While high-field MRI might be the preferred imaging technique in regards to image quality, this does not preclude a use for standing MRI of the hock. In cases where the area of interest is well known from a scintigraphy (Fig 5) or from another diagnostic modality such as radiographs, as was the case in the article by Bolt et al (2013), the use of standing MRI might be preferred and can provide diagnostically useful images. In many geographic areas, standing MRI may be the only modality choice available.…”
Section: Fig 2: T2 Stir Transverse Image Of a Region Of High Signal Cmentioning
confidence: 99%
“…Depending on the specific case, the relative risks vs. reward of the modality choice must be weighed in light of the questions that are being asked. In the article by Bolt et al (2013) in this issue, the authors describe a case in which a recovery accident from a general anaesthetic resulted in a significant injury to the central tarsal bone of the hock. Radiographic evaluation identified the lesion, but the severity and anatomical configuration of the fracture was difficult to ascertain with certainty.…”
mentioning
confidence: 99%